The Impact of Cloud-Based Information Systems on Organizational Performance in Education: A PIECES Framework Evaluation in Bekasi City - Sumardiono Sumardiono; Rika Apriani; Sigit Setiawan; Fazril Mantovani; Reykhando Rifki Awiliyanto; Adrianus Trigunadi Santoso (Institut Teknologi Dirgantara Adisutjipto, 2026)
This study aims to evaluate the impact of cloud-based information system implementation on organizational performance in the education sector, particularly in Bekasi City. The method used is descriptive-quantitative with the PIECES framework approach (Performance, Information, Economy, Control, Efficiency, Service). Data were collected through questionnaires and interviews with 10 respondents consisting of education service operators, teachers, and school operators. The results show that five PIECES dimentions—namely Performance (4.38), Information (4.22), Economy (4.20), Efficiency (4.33), and Service (4.35)—are in the very satisfactory category. However, the Control dimention only obtained a score of 2.85, which is included in the neutral category, indicating weaknesses in system security governance. This study concludes that although cloud systems have improved operational efficiency and service quality, regular information system security audits and the development of standard operating procedures (SOPs) are needed to strengthen the control dimention. The implications of this study serve as a basis for developing better information security governance in the digital transformation of education.